Creativity and opportunity: how COVID-19 fosters digital dance education. Issue 3 (3rd July 2021) - Li, Zihao (Michael)
ABSTRACT: The COVID-19 pandemic has caused major disruptions to every sector, including education. Virtual space during the pandemic has enabled a range of creative events, such as streaming performances, cyber tours, and online activities. Within confined spaces, performing artists have quickly become digital experts in pushing boundaries. This paper examines how tertiary dance teachers and students have coped with the sudden change caused by the COVID-19 pandemic. A total of 120+ university/college dance teachers and students from different continents participated in this study. The study finds that some technologies work better than others, virtual platforms are congruent with current students' learning preferences, and restrictions in space boost creativity and empathy. This paper shares timely lessons and insights on tools, pedagogies, and strategies for online teaching and learning. It aims to foster further discussions and interrogations of how far we can push practice-based subjects in education by creatively engaging digital technology.